PkM WORKSHOP PELUANG KARIR MELALUI PENDIDIKAN TINGGI PADA SISWA SMK ISLAM AR-ROYYANNA KAWUNGANTEN KABUPATEN CILACAP - Yudi Agus Setiawan; Mutia Pamikatsih; Elok Ainur Latif; Syafi’ah; Suwono; Norma Eralita (Arunika: Jurnal Pengabdian Masyarakat, 2025)
This Community Service aims to increase awareness and interest of regarding the importance of continuing their education to tertiary level. Vocational Schools are designed to produce work-ready graduates, the increasingly complex dynamics of the global job market demand competencies that are more than just technical skills. This outreach activity is carried out through interactive presentations, question and answer sessions, and student mentoring, which includes information about career prospects with higher education, various relevant academic study paths, as well as tips for preparing for selection and scholarships. This community service method is designed with an educational-participatory approach, which means we not only provide information, but also actively involve students in the socialization process. The results of the activities showed an increase in students' understanding of the long-term benefits of higher education, a positive shift in perceptions regarding options after graduating from vocational school, as well as a growing motivation to explore further information about further studies. It was concluded that comprehensive and sustainable socialization is very necessary to broaden the horizons of students, so that they can make more informed and strategic career decisions for a better future. This service provides an educative-participatory approach which is an effective strategy for opening students' insight into higher career potential in the future.